2013
DOI: 10.5021/ad.2013.25.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Familial Colocalization of Lichen Planus and Vitiligo on Sun Exposed Areas

Abstract: Lichen planus and vitiligo are common skin disorders. Colocalization which is rarely reported may consider the koebner phenomenon related to the photo damage causing initiation of lichen planus over vitiliginous skin. We report a 37-year-old mother and her 23-year-old daughter, both farmers and known cases of vitiligo with subsequent gradual onset of pruritic skin lesions of lichen planus starting first over previous vitiliginous skin on sun exposed areas. Coexistence and colocalization of lichen planus and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 7 publications
0
13
0
5
Order By: Relevance
“…Additionally, there are several reports describing lesions of LP that developed mainly over sun-exposed vitiliginous skin [25,26,29,30,31]. Extrapolating this to FFA, actinic damage in vitiliginous skin may trigger initiation of FFA on vitiligo-affected skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there are several reports describing lesions of LP that developed mainly over sun-exposed vitiliginous skin [25,26,29,30,31]. Extrapolating this to FFA, actinic damage in vitiliginous skin may trigger initiation of FFA on vitiligo-affected skin.…”
Section: Discussionmentioning
confidence: 99%
“…Lichen planus (LP) has been previously associated with vitiligo [23,24,25,26,27,28,29,30,31]. Furthermore, some authorities consider FFA as a variant of LPP [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Baghestani i wsp. [6] opisali współwystępowanie dermatoz u matki i cór-ki. Zaledwie jeden opis dotyczył okolic genitalnych (moszny) [7].…”
Section: Listy Do Redakcjiunclassified
“…In our case hyperkeratotic LP was associated with vitiligo. S. Baghestani et al have reported familial coexistence of LP and vitiligo, correspondingly, J. Wyte et ala case of long-standing vitiligo that was spared in LP [22,23]. G. Kravvas et al reviewed many theories of LP association with vitiligo as sun-exposed depigmented areas play an important part in the initiation of LP; the evident manifestation of the Koebner phenomenon in vitiligo area.…”
mentioning
confidence: 99%